2005
DOI: 10.1182/blood-2004-03-1095
|View full text |Cite
|
Sign up to set email alerts
|

Tissue-factor–bearing microvesicles arise from lipid rafts and fuse with activated platelets to initiate coagulation

Abstract: Tissue factor (TF) circulates in plasma, largely on monocyte/macrophage-derived microvesicles that can bind activated platelets through a mechanism involving P-selectin glycoprotein ligand-1 (PSGL-1) on the microvesicles and P-selectin on the platelets. We found these mi-crovesicles to be selectively enriched in both TF and PSGL-1, and deficient in CD45, suggesting that they arise from distinct membrane microdomains. We investigated the possibility that mi-crovesicles arise from cholesterol-rich lipid rafts an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

27
742
2
12

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 912 publications
(783 citation statements)
references
References 46 publications
27
742
2
12
Order By: Relevance
“…Notably, MVs have a distinct repertoire of lipids not only compared with exosomes (our unpublished data) 41 but also to the plasma membrane of origin. Indeed, MVs are enriched in cholesterol, sphingomyelin and ceramide, and contain lipid raft elements, 28 including GM1 and GM3 gangliosides and flotillin-2. 42 Accordingly, artificial liposomes, composed of the main phospholipids of the plasma membrane, neither induce fibril solubilization nor promote Ab neurotoxicity.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Notably, MVs have a distinct repertoire of lipids not only compared with exosomes (our unpublished data) 41 but also to the plasma membrane of origin. Indeed, MVs are enriched in cholesterol, sphingomyelin and ceramide, and contain lipid raft elements, 28 including GM1 and GM3 gangliosides and flotillin-2. 42 Accordingly, artificial liposomes, composed of the main phospholipids of the plasma membrane, neither induce fibril solubilization nor promote Ab neurotoxicity.…”
Section: Discussionmentioning
confidence: 99%
“…This sorting mechanism may be consistent with the proposed role of lipid rafts in setting up platforms to concentrate into MVs proteins destined to secretion. 28,56 Finally, processing of Ab 1-42 to Ab 1-40 may even proceed within MVs. Indeed, previous evidence showed that neuron-derived EMVs contain some components of the gsecretase complex, 57 whereas the insulin-degrading enzyme, which proteolyzes Ab 1-42 and Ab 1-40, has been detected among cargo proteins of microglial EMVs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We investigated whether the disruption of lipid rafts from trophozoite plasma membranes affected MV formation, as it was defined previously (Del Conde et al, 2005). To assess this effect, we treated trophozoite Results are representative of two independent experiments.…”
Section: The Origin Of Microvesicles Is Plasma Membrane and Lipid Rafmentioning
confidence: 99%
“…Different reports have shown that cholesterol should influence the lipid raft microdomains on the membrane that participate in MV formation. An interesting report by Del Conde et al (2005), demonstrated that the coagulation process is dependent of the transference of tissue factors released from monocyte-MVs to platelets. This release is dependent of lipid raft microdomains.…”
Section: Microvesicle Release Is Associated With Lipid Rafts and Mvsmentioning
confidence: 99%